(untitled) (International Journal of Engineering and Computer Science, 2015)
Steganography technique plays an important role in information hiding in any digital cover object. Security of information on internet against unauthorized access has become a prime problem. Due to this, steganography technique becomes more popular. Steganography is the science which includes secret communication in an appropriate digital cover objects viz. audio, image, text and video files. The main objective of steganography technique is to hide the presence of the embedded information in carrier file and other objectives are robustness, Un-detectability and capacity of the concealed data. Steganography is separate from other related techniques viz. watermarking and cryptography in term of robustness and Un-detectability of information. Watermarking is a technique that hides information in digital image to protect intellectual properties and copyright, such as logo for proving ownership. Steganography and watermarking are important techniques to conceal important data in cover object an undetectable and irremovable way. Both techniques are the fast developing area of information hiding. This paper delivers a comparative study on digital images steganography and watermarking techniques and significant research growths are also discussed.